2017
DOI: 10.1007/s13311-017-0524-0
|View full text |Cite
|
Sign up to set email alerts
|

Brain Cancer Stem Cells in Adults and Children: Cell Biology and Therapeutic Implications

Abstract: Brain tumors represent some of the most malignant cancers in both children and adults. Current treatment options target the majority of tumor cells but do not adequately target self-renewing cancer stem cells (CSCs). CSCs have been reported to resist the most aggressive radiation and chemotherapies, and give rise to recurrent, treatment-resistant secondary malignancies. With advancing technologies, we now have a better understanding of the genetic, epigenetic and molecular signatures and microenvironmental inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 118 publications
(128 reference statements)
0
76
0
Order By: Relevance
“…A small number of CSCs were able to form tumors in non-obese diabetic/severe combined immunodeficient mice in vivo 5 . Interest in CSCs is rapidly increasing during the recent years, and existence of such cells in various of tumors has been verified including prostate 6 , melanoma 7 , lung 8 , liver 9 , breast 10 , brain 11 , pancreas 12 , ovary 13 , mesenchymal carcinomas, 14 and head and neck 15 . In 2007, Prince et al 16 first identified a cellular subpopulation in head and neck tumors expressing the surface marker CD44 with stem-like characteristics; these cells were capable of reproducing when implanted into immunosuppressed mice.…”
Section: Introductionmentioning
confidence: 99%
“…A small number of CSCs were able to form tumors in non-obese diabetic/severe combined immunodeficient mice in vivo 5 . Interest in CSCs is rapidly increasing during the recent years, and existence of such cells in various of tumors has been verified including prostate 6 , melanoma 7 , lung 8 , liver 9 , breast 10 , brain 11 , pancreas 12 , ovary 13 , mesenchymal carcinomas, 14 and head and neck 15 . In 2007, Prince et al 16 first identified a cellular subpopulation in head and neck tumors expressing the surface marker CD44 with stem-like characteristics; these cells were capable of reproducing when implanted into immunosuppressed mice.…”
Section: Introductionmentioning
confidence: 99%
“…Primary brain tumors are a mixture of benign and malignant tumors originating from the brain parenchyma and its surrounding microenvironment [1]. Malignant brain and CNS tumors are the 11 th most common type of cancer and the 3 rd most common cause of cancer mortality [1,2]. Annually, primary brain tumors occur at a frequency of around 7 per 100,000 individuals [2].…”
Section: Introductionmentioning
confidence: 99%
“…Grade IV astrocytoma, called glioblastoma multiforme (GBM), is the most common aggressive type of astrocytoma as well as the most lethal primary brain tumors. GBM has more pronounced malignant features, including uncontrolled cellular proliferation, increased angiogenesis, and resistance to apoptosis [1][2][3]. Therefore, patients diagnosed with GBM have a very poor prognosis with an average survival of 12-15 months post diagnosis [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental models indicate that in GB exists a subpopulation of cells possessing the characteristics of neural stem cells that are responsible for continuous proliferation and drug resistance [ 54 , 55 ]. miRNA profiling revealed that glioma cells have an expression profile remarkably similar to that of embryonic and neural precursor cells and distinct from that of a normal adult brain [ 56 ].…”
Section: The Interplay Between Tumor Suppressing and Oncogenic Mirmentioning
confidence: 99%